2022
DOI: 10.13057/biodiv/d230702
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and species composition of ants at coffee agroforestry systems in East Java, Indonesia: Effect of habitat condition and landscape composition

Abstract: Abstract. Muhammad FN, Rizali A, Rahardjo BT. 2022. Diversity and species composition of ants at coffee agroforestry systems in East Java, Indonesia: Effect of habitat condition and landscape composition. Biodiversitas 23: 3313-3321. Habitat condition and landscape composition are the main factors that shape biodiversity in agroecosystems. However, information on the effect of habitat conditions and landscape composition on biodiversity in agroforestry systems is lacking. Agroforestry systems possess habitats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Differences in entomofauna are the key differences between coffee plantations in Indonesia and South America. In previous studies, Dolichoderus thoracicus was the most dominant ant in coffee plantations, not Azteca (Muhammad et al 2022). The results of this study can be used as recommendations for farmers in the practice of biological control of coffee pests and diseases.…”
Section: Introductionmentioning
confidence: 56%
“…Differences in entomofauna are the key differences between coffee plantations in Indonesia and South America. In previous studies, Dolichoderus thoracicus was the most dominant ant in coffee plantations, not Azteca (Muhammad et al 2022). The results of this study can be used as recommendations for farmers in the practice of biological control of coffee pests and diseases.…”
Section: Introductionmentioning
confidence: 56%
“…This study found that durian and mango were the most dominant species and had roles and benefits for the people of Waraitama Village, where these two fruit plants had high selling value to increase community income. Low species diversity was representated by the diversity index value of <1, moderate species diversity by 1≤H'≤3, and high species diversity by >3 [9,10]. From this classification, it can be seen that the highest species diversity index value is for the Javanese (2.92), followed by the Bugis (2.51), Toraja (2.45), and Papuan (2.29) ethnicities.…”
Section: Composition Of Types Of Woody Plants In the Home Gardensmentioning
confidence: 99%
“…The presence of ants in agroecosystems often depends on landscape heterogeneity and local habitat management. However, few studies have examined biodiversity or local or landscape complexity as ant maintenance drivers, such as those conducted in Central Java Province which focused on plant diversity enrichment (Widhiono et al 2017), while those conducted by Muhammad et al 2022 only focused on habitat condition and landscape composition in coffee agroforestry. Our research aims to investigate the relationship between local habitat modification and landscape composition in maize fields, specifically focusing on their impact on ants species richness, abundance, and species composition.…”
Section: Introductionmentioning
confidence: 99%